PENGARUH SELEKSI DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PADA BAGIAN DIVISI PRODUKSI DI PT. BARATA INDONESIA PERSERO GRESIK - Ibnu Al Avisena (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
This study tries to analyze the influence of selection and job placement on employee performance in the production division at PT. Barata Indonesia (Persero) Gresik which aims to determine the effect of selection and job placement on employee performance in the production division at PT. Barata Indonesia (Persero) Gresik. This type of research is explanatory research. Sampling technique using probability sampling with simple random sampling technique where sampling of member of population have equal opportunity to be taken as sample. Technique of collecting data using kuisoner. Analytical techniques are descriptive analysis and simple linear regression analysis with the help of SPSS 13.0 for windows. This research resulted conclusion that correlation coefficient value 0,454 meaning 45,4% change of employee performance influenced by selection and placement, while the rest is 54,6% influenced by variable or other factor outside model used in this research. Based on hypothesis testing with test of 7,461 and equal to 1,996 so that (7,461> 1,996) at α = 5% can be concluded that variable selection and placement have positive and significant effect to employee performance variable